Closed Gastroschisis: A Rare Abdominal Wall Defect. Issue 3 (March 2022) - Cockrell, Hannah; Shaw, Taylor; Morris, Michael W.
Gastroschisis is a rare congenital abdominal wall defect characterized by intestinal evisceration to the right of the umbilical stalk. In less than 6% of cases, the fascial defect closes around the herniated viscera in utero. The mechanism of fascial closure in these cases is unknown; however, the tourniquet effect on the mesenteric vasculature is thought to lead to intestinal atresia and midgut infarction. We report a case of a female neonate with a prenatal diagnosis of gastroschisis who was found to have a closed defect at the time of delivery. She required emergent operation for symptoms of intestinal obstruction and bowel ischemia.